Generalized purpuric lichen nitidus treated successfully with narrowband UVB therapy - Elli Turjanmaa; Riitta Huotari‐Orava; Niina Korhonen (Wiley, 2023)
Abstract A 66‐year‐old Finnish man suffered from asymptomatic, purpuric skin lesions extending from his ankles and dorsal feet to the trunk and forearms. Based on a skin punch biopsy and the clinical picture, the diagnosis of generalized purpuric lichen nitidus, which is an exceedingly rare form of lichen nitidus, was made. The condition responded well to narrowband UVB phototherapy.